2018
DOI: 10.3389/fonc.2018.00564
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cardiac Sparing in Deep Inspiration Breath-Hold for Patients With Left Sided Breast Cancer

Abstract: Purpose: The purpose of this study was to evaluate patient-related non-dosimetric predictors of cardiac sparing with the use of deep inspiration breath-hold (DIBH) in patients with left-sided breast cancer undergoing irradiation (RT).Materials and Methods: We retrospectively reviewed charts and treatment plans of one-hundred and three patients with left-sided breast cancer. All patients had both free-breathing (FB) and DIBH (with body surface tracking) plans available. (MHD) and V4 (heart volume receiving at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Several groups have attempted to identify simple predictors of cardiac sparing during DIBH for patients with LSBC, but no clear factors have emerged. Age, amplitude, body mass index, and smoking status have been investigated, yet only body mass index appears to be an indicator of when DIBH would be preferred 41–44 . Jacobson et al reported that older patients are generally not as eligible for DIBH as are younger patients 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have attempted to identify simple predictors of cardiac sparing during DIBH for patients with LSBC, but no clear factors have emerged. Age, amplitude, body mass index, and smoking status have been investigated, yet only body mass index appears to be an indicator of when DIBH would be preferred 41–44 . Jacobson et al reported that older patients are generally not as eligible for DIBH as are younger patients 43 .…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting findings in previous studies regarding the relationship between patient-specific factors and effective deep breath holding (18,25,26,29) . In a Japanese cohort, they found that a relative reduction in the mean heart dose correlated with inspiratory volume (25) .…”
Section: Discussionmentioning
confidence: 97%
“…The differences may arise from the discrepancy in the total dose prescription and the size of the radiation field, CTV definition and size, OAR contouring, including diameter of the coronary arteries and LV thickness, the lack of detailed heart contouring atlases, individual coronary topology, heart size, body mass index, CWS distance, and finally radiotherapy technique used. 9,33,[49][50][51][52] The use of contrast agent 53 or automatic substructures' segmentation without 54 or with cardiac magnetic resonance imaging 55 could improve contouring consistency, but these technical solutions are unlikely to be widely adopted in the near future. Non-automatic contouring is feasible as showed in a study by Francolini et al Authors made multiple comparisons of delineated cardiac chambers and 5 left LV wall segments according to aforementioned cardiac atlas 24 and confirmed high interobserver delineation consistency.…”
Section: Discussionmentioning
confidence: 99%